Postoperative Incidence of Iatrogenic Gallbladder Perforation During Laparoscopic Cholecystectomy in Sulaimaniyah Teaching Hospital - Sarkhel Hama Tofiq; Seerwan Hama Shareef (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background and Objective: Iatrogenic perforation of the gallbladder has been reported in 28% of those patients who undergo laparoscopic cholecystectomy. It has been pointed out that gallbladder perforation can result in formation of gallstones and spillage of bile. The present study was carried out in order to investigate the postoperative incidence of iatrogenic gallbladder perforation during laparoscopic cholecystectomy in SulaimaniTeaching Hospital.Patients and Methods: The present investigation was a single center, retrospective observational study that was carried out in Sulaimani Teaching Hospital in 2018-2019. The study sample included 99 patients who had undergone elective cholecystectomy. Required data on the possible risk factors and early outcomes and the patients’ demographics including age, BMI, and gender were collected. The collected data were analyzed through the Statistical Package for the Social Sciences (version 22.0).Results: The results revealed that 80% of the patients were females. Also, 42.4% had no chronic diseases, while diabetes mellitus (DM), DM along with hypertension (HT), and HT were found to be the most prevalent chronic diseases among them with 18.2%, 16.2%, and 10.1% of prevalence, respectively. Only 17.2% of the patients had abdominal operation before, and acute cholecystitis and chronic cholecystitis were seen respectivelyin 13% and 17% of them. The most common causes of gallbladder perforation (GP) were found to be electrocautery(16.2%) and grasper (7.1%). Moreover, 33.3% of the patients were overweight (BMI between 25 and 29.9), 45.5% were obese (BMI between 30 and 34.9), and 20.2% had BMI of over 35. Most of the patients aged 30 to 49 (62.6%). A majority of the patients (94.9%) were found to have gallstones.Conclusion: Iatrogenic gallbladder perforation is prevalent among patients who undergo laparoscopic cholecystectomy. However, laparoscopic cholecystectomy is still a better choice and associated with fewer complications compared to open cholecystectomy. Required measures need to be adopted for patients with perforated gallbladder in order to minimize spillage and remove as much spilled gallbladder content as possible.